2021
DOI: 10.1155/2021/6652791
|View full text |Cite
|
Sign up to set email alerts
|

A Cornflower Extract Containing N-Feruloylserotonin Reduces Inflammation in Human Skin by Neutralizing CCL17 and CCL22 and Inhibiting COX-2 and 5-LOX

Abstract: Thymus and Activation-Regulated Chemokine (TARC/CCL17) and Macrophage-Derived Chemokine (MDC/CCL22) are two key chemokines exerting their biological effect via binding and activating a common receptor CCR4, expressed at the surface of type 2 helper T (Th2) cells. By recruiting Th2 cells in the dermis, CCL17 and CCL22 promote the development of inflammation in atopic skin. The aim of this research was to develop a plant extract whose biological properties, when applied topically, could be beneficial for people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…First, to development of prevention and treatment materials in AD, further studies are needed to focus on the neuroprotective effects of FS under in vivo system such as animal and clinical studies. Previous studies have demonstrated beneficial effects of FS such as anti-inflammatory effect and anti-atopic dermatitis under in vivo system [ 17 , 67 ]. However, in the current stage, lack of enough data to support the neuroprotective effect of FS under in vivo system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, to development of prevention and treatment materials in AD, further studies are needed to focus on the neuroprotective effects of FS under in vivo system such as animal and clinical studies. Previous studies have demonstrated beneficial effects of FS such as anti-inflammatory effect and anti-atopic dermatitis under in vivo system [ 17 , 67 ]. However, in the current stage, lack of enough data to support the neuroprotective effect of FS under in vivo system.…”
Section: Discussionmentioning
confidence: 99%
“…N -feruloyl serotonin (FS; Figure 1 ) belongs to polyphenols [ 14 ], is a member of serotonin derivatives found in the seeds from safflower and Leuzea carthamoides , and cornflower [ 15 , 16 , 17 ]. Previous findings have revealed that FS exerts health beneficial effects such as anti-inflammation, antioxidant, and anti-apoptotic properties [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory properties of cornflower flowers were confirmed by pharmacological experiments 10 . Cornflower extracts inhibited cyclooxygenase 2 (COX-2) and 5-lipoxygenase (5-LOX) and had anti-inflammatory activities mainly due to the presence of N-feruloylserotonin (able to inhibit 5-LOX and COX) 41 , whereas apigenin was the most effective XO inhibitor identified in C. virgata Lam 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oral administration of ESM reversed the UVB-induced elevation in cytokine expression (Fig. 5A), and reduced the mRNA expression of cyclooxygenase-2 (COX-2), which is the enzyme responsible for causing inflammation (Carola et al 2021). Next, we investigated the expression levels of antioxidant enzymes to confirm their relation to the suppression of cytokine expression in the ESM-treated group.…”
Section: Oral Administration Of Eggshell Membrane Reduces Uvb-induced...mentioning
confidence: 91%